Elaboración de un panel tradicional de hormigón adicionando cenizas de cáscara de cacao - Caicedo Ayala, Alfonso Mauricio (2024)
The thesis examines the problem of the generation of cocoa shell waste in the food industry and proposes an innovative solution for its reuse in construction. It focuses on the use of cocoa shell ash as an aggregate in the concrete mix for the production of modified traditional panels. The primary objective is to reduce the environmental impact of this waste and promote sustainable practices in the construction industry. The research focuses on analyzing the performance of the modified panels, evaluating their resistance, durability and thermal properties. A comprehensive study is carried out that includes the determination of optimal quantities of material, laboratory tests and economic analysis. The results reveal that the addition of cocoa shell ash significantly improves the properties of concrete, offering panels with improved characteristics and a lower environmental impact. Additional benefits are identified such as the promotion of more sustainable construction practices. The use of cocoa shell ash in the construction of concrete panels represents a viable and promising alternative, with the potential to contribute significantly to the mitigation of environmental problems and the development of a more sustainable and efficient construction industry.